THE EFFECTS OF STEM BLEEDING DISEASE ON THE FLOWERING AND FRUIT SETTING OF COCONUT HYBRID PB 121 - J. Brahmana (International Coconut Community Journal, 1986)
Stem bleeding is one the common diseases of coconut in Indonesia. The severity of the disease varies considerably depending on the cultivars, environmental. factors, and the occurence of mechanical. damage on the stem. Observation on the coconut hybrid PB 121 in the Bangun Purba estate PTP VI North Sumatra indicated that stem bleeding disease caused‑necrosis in the stem tissue but it did not kill the tree. Moreover, this disease had no negative effects in the flowering, fruiting and inflorescence formation of the coconut tree.